Adolescent Identity Treatment An Integrative Approach for Personality Pathology - Foelsch, Pamela A.; Schlüter-Müller, Susanne; Odom, Anna E.; Arena, Helen T.; Borzutzky H., Andrés; Schmeck, Klaus (Springer International Publishing : Imprint: Springer, 2014)
Adolescent Identity Treatment: An Integrative Approach for Personality Pathology is a groundbreaking title that provides general and specific clinical strategies to help adolescents who lack an integrated identity.  The authors have developed a treatment based on the integration of object relations theory, family systems, attachment, developmental neurobiology and cognitive behavioral approaches that focuses on clearing blockages to normal identity development and  adaptive functioning. While most adolescents build satisfying interpersonal relationships, are successful in school and work, and begin romantic relationships, there is a minority of adolescents who do not succeed in this and are at a high risk of developing problems in school, work, and relationships,  problems with affect regulation as well as engaging in a wide range of self-destructive behaviors. In addition to a description of the disorder and assessment, this manual offers extensive clinical examples and concrete interventions, with phase-specific treatment components, including a clear treatment frame, psychoeducation, environmental interventions (with a "Home Plan" that addresses self-care behaviors, responsibilities and improved boundaries that fosters the development of better relationships between the adolescent and family), and parenting strategies, all in the service of creating a space for the individual work with the adolescent.